Pelatihan Hybrid Metode Takakura untuk Mendukung Pengelolaan Sampah Organik Berkelanjutan di Desa Awan, Kintamani, Bangli - I Kadek Sartika; Ida Ayu Kinanti Trigayanti; Maesya Putri Nabilla; Ni Komang Okin Pradnyantari; Ni Made Pradnyani Bulan Mahandari (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2026)
This community service activity aimed to describe the implementation and initial outcomes of hybrid training in organic waste management using the Takakura method in Awan Village, Kintamani District, Bangli Regency, Bali. The activity was conducted on July 4, 2026, using a participatory approach that combined online education and onsite practice. A total of 114 university students participated in the activity, consisting of 60 online participants through Zoom Meeting and 54 onsite participants. All participants attended a talk show on organic waste management, while onsite participants also joined demonstrations, discussions, and compost-making practice. The evaluation was conducted descriptively through observations of participation, discussion engagement, the ability to follow composting stages, and activity outputs. The onsite participants were divided into five groups and produced five Takakura compost baskets. Online education expanded the dissemination of information, whereas onsite practice provided direct experience in preparing materials, arranging the composting medium, mixing organic waste, and understanding basic compost maintenance. The results indicate that hybrid training can combine knowledge dissemination with technical skills learning. However, because the activity did not include measurements before and after the program or long-term monitoring, the findings were limited to implementation outcomes and participants’ initial skills. Follow-up assistance is needed to monitor compost maturity, the continued use of the baskets, and the application of the Takakura method in the community.